Factor structure and psychometric properties of the Body Appreciation Scale among adults in Hong Kong. (March 2015) - Ng, Siu-Kuen; Barron, David; Swami, Viren
Highlights: Examined factor structure of the Body Appreciation Scale (BAS) in Hong Kong. One- and 2-dimensional models had poor fit. Modified 2-dimensional model had acceptable fit. General Body Appreciation factor had good construct validity. Abstract: Previous research has suggested that the factor structure of Body Appreciation Scale (BAS), a widely-used measure of positive body image, may not be cross-culturally equivalent. Here, we used confirmatory factor analysis to evaluate the conceptual equivalence of a Chinese (Cantonese) translation of the BAS among women ( n = 1319) and men ( n = 1084) in Hong Kong. Results showed that neither the one-dimensional nor proposed two-dimensional factor structures had adequate fit. Instead, a modified two-dimensional structure, which retained 9 of the 13 BAS items in two factors, had the best fit. However, only one of these factors, reflective of General Body Appreciation, had adequate internal consistency. This factor also had good patterns of construct validity, as indicated through significant correlations with participant body mass index, self-esteem, and (among women) actual-ideal weight discrepancy. The present results suggest that there may be cultural differences in the concept and experience of body appreciation.